NOI DIMENSIUNI ALE SECURITĂŢII INTERNAŢIONALE SECURITATEA ENERGETICĂ - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2007)
The energetic security is a new dimension of international security in the contemporary world. Three levels of energetic security can be identified: the national, regional and global energetic security. At the national level every state undertakes independent measures to assure the necessity in the energetic sector. The regional level asks for common actions and programmers of the states. The global level needs the cooperation of all actors of international relations, and good management in the relevant field. For prevention of conflicts between the states in the conditions of limited natural energetic resources, the conclusion, of international treaty of collective energetic security is necessary.